2003
DOI: 10.1016/s0968-0896(03)00119-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimycobacterial activity of new quinoxaline-2-carboxamide 1,4-di-N-Oxide derivatives

Abstract: Abstract:As a continuation of our research and with the aim of obtaining new antituberculosis agents which can improve the current chemotherapeutic antituberculosis treatments, forty-three new quinoxaline-2-carboxamide 1,4-di-N-oxide derivatives were synthesized and evaluated for in vitro antituberculosis activity against Mycobacterium tuberculosis strain H 37 Rv. Active compounds were also screened to assess toxicity to a VERO cell line. Results indicate that compounds with a methyl moiety substituted in posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 14 publications
2
79
0
Order By: Relevance
“…Taking into account the biological values reported in Table 1, it can be concluded that the insertion of a electron-withdrawing moiety, especially that of chlorine atom, is an essential requirement for the anti-tubercular activity, as previously established by our group. [21,22] With the aim of corroborating previous preliminary structure-activity relationship observed by our group and identifying the most suitable length for the aliphatic chain between the carboxamide group and the aromatic ring, three series of compounds (Series 1, 2 and 3) were prepared. Comparing the biological values shown by these compounds, it can be said that the preferred length for the aliphatic chain is one methylene group.…”
Section: Pharmacologymentioning
confidence: 60%
See 2 more Smart Citations
“…Taking into account the biological values reported in Table 1, it can be concluded that the insertion of a electron-withdrawing moiety, especially that of chlorine atom, is an essential requirement for the anti-tubercular activity, as previously established by our group. [21,22] With the aim of corroborating previous preliminary structure-activity relationship observed by our group and identifying the most suitable length for the aliphatic chain between the carboxamide group and the aromatic ring, three series of compounds (Series 1, 2 and 3) were prepared. Comparing the biological values shown by these compounds, it can be said that the preferred length for the aliphatic chain is one methylene group.…”
Section: Pharmacologymentioning
confidence: 60%
“…With regard to position 2, carbonitrile derivatives appeared to be quite toxic [17][18][19][20][21]. Moreover, ketone, carboxylate and carboxamide quinoxaline-1,4-dioxydes derivatives were actually patented in the 70's for their antibacterial activity.…”
Section: Tuberculosis (Mtbc) the Report Published By Who In 2009 Esmentioning
confidence: 99%
See 1 more Smart Citation
“…(61) showed MIC of 6.25 μg/mL against Mtb H37Rv and 0.5 μg/mL against Mtb H37Ra. Which prompted to continue the optimization of quinoxaline 1,4-dioxide [80], a series of quinoxaline-2-carboxamide 1,4-di-N-oxide derivatives were evaluated for their in-vitro anti-TB activity against Mtb H37Rv. Among all, compound 62a exhibited best MIC of 0.78 μM, has a solubility problem, while compound (62b) having MIC of 3.13 μM has a best selectivity index (SI=>40.06).…”
Section: Quinoline and Quinoxaline Derivativesmentioning
confidence: 99%
“…Eleven putative eukaryotic-like protein serine-threonine kinases (Pkn A to L) involved in signal transduction have been identified in M. tuberculosis H37Rv genome (11,(104)(105)(106). Based on this kinase inhibition benzothiophenes (specifically inhibits Pkn G) (107,108) and benzoquinoxalines (inhibitors of Pkn B, Pkn G, and Pkn H) (109)(110)(111)(112) have been reported. Hence this intensive research on signaling kinase inhibitors could also provide target oriented lead molecules for the control of tuberculosis.…”
Section: 24-benzothiadiazinesmentioning
confidence: 99%